Multimodality planning of stereotactic radio-ablation for ventricular tachycardia. Results from the international MUSIC consortium. (19th May 2022) - Cochet, H; Tedrow, U; Maury, P; Whitaker, J; Woods, C; Gandjbakhch, E; Khalifa, J; Bredfeldt, J; Mak, R; Sauer, W; Sermesant, M; Sacher, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Council Background: Optimal SBRT planning methods for VT ablation are yet to be defined. Purpose: To evaluate a multimodal approach for SBRT planning. Methods: 30 pts (age 70±10, 90% men, LVEF 26±9%, 67% ICM, 47% NICM or mixed, 1.7±1.2 prior catheter ablations) with drug-refractory VT underwent imaging prior to SBRT. The inHEART technology was used to create image-based 3D models of substrate, cardiac anatomy, and organs at risk (coronaries, phrenic nerve, GI tract, AV node). In MUSIC software (IHU Liryc-Inria), 3D models were fused with prior EP maps, and SBRT targets were interactively drawn in 3D by the referring EP cardiologist. Transmural target volumes and organs at risk were fused with a 4D planning CT and used to plan SBRT in Eclipse (Varian). Results: SBRT was delivered on median PTVs of 96[63-149] mL (total dose 25 Gy) with either Truebeam or Edge systems (Varian). Over a median FU of 4[2-8] months, death occurred in 11(37%) pts, due to arrhythmia recurrence in 4(13%). FU at 6 months was available in 14 pts. In these, the median numbers of VT episodes and ICD shocks over the 6 months preceding SBRT were 20[9-27] and 8[5-15], respectively. In the 6 months following SBRT, these decreased to 0[0-30] and 0[0-0], respectively (P<0.001 for both). 8/14(57%) pts were free from any VT recurrence, and 11/14(79%) were free from any ICD shock. In the total cohort, complications attributed to SBRT were observed in 2/30 (7%), none of which were fatal (heart failure and pneumonitis, both managed with steroids). Conclusion: In patients with severe drug- and catheter ablation-refractory VT, SBRT planning based on 3D image-based models fused with prior EP maps is feasible, and associated with favorable efficacy and safety profiles.